Motivation for participation in sports among Brazilian adults: National Household Sample Survey - 2015 - Andrea Wendt; Luiza Isnardi Cardoso Ricardo; Caroline dos Santos Costa; Francine dos Santos Costa; Thaynã Ramos Flores; Rosália Garcia Neves; Grégore Iven Mielke (2021)
Abstract This article aims to describe the reasons for sport participation in the Brazilian adult population according to gender, age and schooling level. This is a cross-sectional study with data from a National Household Sample Survey - 2015. The reasons to practice or not practice sports in the previous year were obtained by questionnaire with predetermined answer options. All analyses were performed in Stata 12.1 and stratified by gender. The prevalence of sports participation for men and women were 31.7% and 16.9%, respectively. The most frequent reasons for sports participation among men were: having fun, quality of life and performance. Among women, the most frequent reasons were: quality of life, performance and medical recommendation. Regarding reasons for not practicing sports, the most reported ones were: lack of time (38.8% for men and 37.8% for women), not enjoying (34.8% for men and 35.3% for women) and health problem (20.3% for men and 17.9% for women). The study findings showed the most frequent reasons for sport participation in Brazil. Understanding these reasons and how they affect different age ranges and educational levels may contribute to improve strategic planning to promote sports in middle-income countries.